Managing virtual network embedding through reconfiguration and expansion. (November 2019) - Araújo, Samuel Moreira Abreu; Guidoni, Daniel Ludovico; de Souza, Fernanda Sumika Hojo; Mateus, Geraldo Robson
Network virtualization concerns an important issue for the future internet. There have been many advances in the state of the art, but there are still challenges to be explored. The virtual network embedding problem is one of these, and is an NP-hard problem. Aiming to improve the embedding task, reconfiguration and expansion appear as possible strategies for the service provider. In this work, we explore the management of resources in order to improve the acceptance of requests deciding when and how reconfiguration and expansion shall apply. An exact approach based on integer linear programming along with a heuristic approach is evaluated. Simulation results indicate both reconfiguration and expansion strategies are able to improve the acceptance, but reconfiguration should be considered first as it can provide significant improvements in managing the fragmentation problem. Expansion comes as a secondary decision if necessary.